Supply-chain roadmapping - Yee, Choy Leong (2012)
This paper aims to develop a supply chain roadmapping technique for managers to map, visualize, and analyze strategies of multiple firms operating in a supply chain. The integration and alignment of strategy between suppliers, manufacturers, and customers to maintain competitive in business is getting more importance in today’s global market, Thus it is important for managers to focus on multiple players and complex strategic decisions in the whole supply chain. The questions of how could managers manage their supply chain that involves a wide range of competing and cooperating firms; and how could managers analyze strategies of a collective of vertically related companies at a variety of different situational settings, are of interest to many managers. So far, little is available to assist managers in analyzing strategies of a supply chain. In order to address this gap, a supply chain roadmapping technique is adopted and tested in a wide range of companies using action research. A live industrial case study is used to demonstrate the application of the technique. This paper reports the findings and is structured into five parts. Firstly, this paper reviews the literature on supply chain strategy. Then, it describes the underlying concepts and stages of the supply chain roadmapping technique. Thirdly, the action research use in this research is illustrated. Fourthly, the application of the technique in a live industrial setting is described, and the results are presented. Finally, the paper concludes by discussing the implications of this work to managers and academics.